Mangroves- a Potential Phyto-Remediator and Useful Bio-Indicator against Heavy Metal Toxicity - Gupta, Suparna; Chakrabarti, S. K. (International Journal of Bio-resource and Stress Management, 2023)
Mangroves, the tropical and sub-tropical estuarine eco-system is now under severe threat, of which environmental pollution plays an important role in decreasing the species diversity. The present investigation was undertaken to generate information on the effect of some heavy metals (Hg, Pb, and Cd) on two dominant mangroves of sunderban viz., Bruguiera sexangula and Ceriops decandra. In both the mangrove species, roots accumulated more heavy metals than stem and leaf linearly correlated with the reduction in growth parameters and the mode of heavy metal accumulation was in the order of Cd>Pb>Hg. Potentiality of Bruguiera sexangula and Ceriops decandra to grow, establish and thrive within the polluted environment could be effectively used for phyto-remediation, however Bruguiera was found to be more suited. The visible toxicity symptoms i.e. browning of shoot tip in case of Hg, yellowing of leaves for Pb, chlorosis for Cd etc could be efficiently used as bio-marker or bio-monitor or bioindicator in the heavy metal polluted environment. Activity assessment of the most important stress enzyme peroxidase (POD) clearly indicated that a linear relationship between POD activity and leaf tissue metal concentration was found upto concentration 3 (2 times more than the permissible limit) level of all the three heavy metals at 100 DAS for both the mangrove species, but at concentration 4 (4 times more than the permissible limit) a sudden decrease in activity was noticed, which is surprisingly associated with the visible toxicity symptoms.